β-Glucan Combined With PD-1/PD-L1 Checkpoint Blockade for Immunotherapy in Patients With Advanced Cancer - Wang, Mengjie; Bai, Yu; Pei, Jiaxin; Li, Dongqing; Pu, Xiaolin; Zhu, Wenyu; Xia, Lei; Qi, Chunjian; Jiang, Hua; Ning, Yongling (Frontiers in Pharmacology, 2022)
Programmed death-1 (PD-1)/PD-ligand 1 (PD-L1) checkpoint blocking antibodies have been shown to be a powerful immune checkpoint blockade (ICB) therapy for patients with cancer. However, patients quickly develop resistance to immunotherapy. β-glucan, an immune adjuvant, has been found to stimulate innate and adaptive immune responses. In this study, we assessed the use of whole glucan particle (WGP) β-glucan in combination with PD-1/PD-L1–blocking antibodies to slow resistance to immunotherapy. Results from a tumor mouse model demonstrated that administration of WGP β-glucan plus PD-1/PD-L1–blocking antibodies led to increased recruitment of immune-associated cells, improved regulation of the balance between T-cell activation and immune tolerance, and delayed tumor progression. This combination therapy was also found to improve progression-free survival in patients with advanced cancer who had previously discontinued anti-PD-1/PD-L1 because of disease progression. These findings suggest that β-glucan could be used as an immune adjuvant to reverse anti-PD-1/PD-L1 resistance by regulating the immune system.